Konten Edukatif di Instagram: Studi Kasus Tasya Farasya Approved - Febriansis, Diva; Yulianti Fajar Wulandari; Ali Imron Hamid (Brand Communication, 2025)
Social media today serves not only as a means of communication and entertainment, but has also become a space for people to obtain information and knowledge. Instagram, as one of the most popular visual platforms, has given rise to the phenomenon of influencers who play a significant role in shaping public opinion. One prominent figure is Tasya Farasya, a beauty influencer known for her "Tasya Farasya Approved" content on her Instagram account. This study aims to analyze the extent to which the content produced contains educational value for the public. The study used a qualitative approach with a content analysis method on a number of posts over a certain period. The results show that Tasya Farasya's content is not only product promotion but also includes elements of public education in the form of explanations of ingredients, functions, how to use, and ethical considerations in choosing products. Analysis using the Two-Step Flow of Communication and Social Learning theories shows that Tasya Farasya acts as an opinion leader who not only conveys information from manufacturers but also interprets it in language that is easily understood by the public, resulting in a two-step communication flow that strengthens public understanding. This study concludes that the role of influencers can go beyond commercial functions to become an educational tool, particularly in the field of beauty literacy.